Computational studies of Brønsted acid-catalyzed transannular cycloadditions of cycloalkenone hydrazones - Pedrón, Manuel; Sendra, Jana; Ginés, Irene; Tejero, Tomás; Vicario, Jose L.; Merino, Pedro (Beilstein Journal of Organic Chemistry, 2023)
The contribution to the energy barrier of a series of tethers in transannular cycloadditions of cycloalkenes with hydrazones has been computationally studied by using DFT. The Houk's distortion model has been employed to evaluate the influence of the tether in the cycloaddition reaction. That model has been extended to determine the contribution of each tether and, more importantly, the effect exerted between them. In addition to the distortion induced by the tethers, the entropy effects caused by them has also been studied. The analysis of the evolution of the electron localization function along the reaction revealed the highly concerted character of the reaction.
Keywords: DFT; distortion model; hydrazones; transannular cycloadditions